Decentralized renewable energy futures trading on EVM blockchains - Ho, Phi Dung (Nanyang Technological University, 2024)
The transition to decentralized energy trading on the blockchain necessitates a sophisticated design of an efficient market-making mechanism to accommodate the high cost of blockchain transactions. Previous models based on double auctions [1] exhibit several limitations in capturing the complexity of an energy marketplace. This report introduces a Requests for Quote (RFQ) model as a novel market-making protocol for the decentralized energy marketplace, particularly for the Forward/Future, Balancing, and Capacity market. The primary focus of this research is the design and development of an RFQ marketplace for renewable energy futures trading on the blockchain. The key contributions of this work include the integration of the RFQ market-making mechanism into a blockchain-based P2P DER trading platform and the empirical evaluation of the protocol’s effectiveness through a benchmark analysis. The RFQ model presented in this report aims to address the limitations of existing market-making mechanisms and provide a more suitable solution for decentralized energy trading on the blockchain. To demonstrate the feasibility and functionality of the proposed RFQ model, a mock version will be deployed on the Sepolia testnet, serving as a proof-of-concept for the potential of the RFQ model in facilitating efficient and secure renewable energy futures trading